An entrepreneurial key competencies' model - Labib Arafeh (Journal of Innovation and Entrepreneurship, 2016)
The paper has twofold goals. The paper reviews the culture of entrepreneurship and entrepreneurial competencies in Palestine. It is characterized by donor-supported and non-governmental-initiated trainings. This demands an urgent active involvement of universities in the field of entrepreneurship that is shaped in the form of Research and Development as well as offering entrepreneurship academic programs. This comes in line with the emerging trend of offering courses and programs at universities worldwide. Furthermore, the paper proposes a softcomputing-based entrepreneurial key competencies' model (SKECM). This tool is capable of predicting/judging the overall quality of entrepreneurial competencies. SKECM is based on the three-cluster, ten key entrepreneurial competencies developed and used by Empretec. A three-stage, 14 different models have been developed and validated by hundreds of randomly generated datasets. Measures were used to validate the adequacy of these models including, the mean average percentage errors and the maximum percentage errors. The best achieved values for these measures are 0.8511 and 6.3175, respectively. However, although the preliminary findings of the proposed SKECM model are promising, more testing is still required before stating the adequacy of applying the softcomputing modeling approach in the entrepreneurship field (This is to state that there are no financial competing interests (political, personal, religious, ideological, academic, intellectual, commercial, or any other) to declare in relation to this manuscript).
Keywords: 650; Entrepreneur; Competencies; Key entrepreneurial competencies; Neurofuzzy; Softcomputing; Modeling; Model